دور المؤسسات الصغيرة والمتوسطة في تحقيق الإقلاع الاقتصادي - جليل, مونية (Université de M'sila,univ-msila.dz, 2018)
In view of international trends in the globalization of economic activities and to achieve openness between markets and the implementation of free competition, it has become necessary to rely on small and medium enterprises, and to focus on their role in achieving of growth and development, and considering the possession of efficiency and speed to cope with the economic environment variables unlike the previous outlook, which consider industries and large enterprises as a portal for overall economic development. It has become inevitable today in the world to focus on investment policy in small and medium-sized enterprises according to its important role in the development of the economy in general and the industrial sector in particular, thanks has its economic and social benefits and characteristics that will enable them to make a significant contribution to reducing unemployment and increasing the value added of the economy, provided that the environment is conducive to growth in light of the international trends of globalization. The purpose of this study is to try to highlight the role and importance of these institutions and their contribution to economic and social development, as well as the depth of the challenges that the development and survival of these companies are facing in Algeria. in particular the negative role of banks, which have practically discouraged investors through a bureaucratic and counter-productive lending policy.
Keywords: free competition, small and medium nterprises, growth, development, economy.